Відповідь:
14
Пояснення:
x²(3 - x) - (2 - x²)(x + 1) - 4x² = 3x² - [tex]x^{3}[/tex] - ( 2x-[tex]x^{3}[/tex] + 2-x²) - 4x² = 3x² - [tex]x^{3}[/tex] - 2x+[tex]x^{3}[/tex] -- 2+x² - 4x² = -2x + 2
якщо х = -6, -2*(-6) +2= 12+2=14
розрахунки
(2 - x²)(x + 1) = 2x-[tex]x^{3}[/tex] + 2-x²
3x² +x² - 4x² = 0
- [tex]x^{3}[/tex]+[tex]x^{3}[/tex] = 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
14
Пояснення:
x²(3 - x) - (2 - x²)(x + 1) - 4x² = 3x² - [tex]x^{3}[/tex] - ( 2x-[tex]x^{3}[/tex] + 2-x²) - 4x² = 3x² - [tex]x^{3}[/tex] - 2x+[tex]x^{3}[/tex] -- 2+x² - 4x² = -2x + 2
якщо х = -6, -2*(-6) +2= 12+2=14
розрахунки
(2 - x²)(x + 1) = 2x-[tex]x^{3}[/tex] + 2-x²
3x² +x² - 4x² = 0
- [tex]x^{3}[/tex]+[tex]x^{3}[/tex] = 0